Mapping Digital Assessment Platforms in EFL Classrooms: A Qualitative Case Study at an Islamic Junior High School - Edy Waloyo; Nida’ul Hasanah; Wakhid Nashruddin (STIT Buntet Pesantren Cirebon, 2025)
The growing integration of digital technology into English language education has encouraged teachers to adopt various digital platforms for classroom assessment. However, previous studies have predominantly examined the effectiveness of individual applications, with limited attention to how teachers employ multiple digital assessment platforms within their professional assessment practices. This study aimed to identify the digital assessment platforms employed by English teachers in an Islamic junior high school. A qualitative case study was conducted at an Islamic junior high school in Cirebon, Indonesia, involving two English teachers selected through purposive sampling. Data were collected through semi-structured interviews, classroom observations, and document analysis and analyzed using Braun and Clarke's thematic analysis. The findings identified three complementary categories of digital assessment platforms: institutionalized assessment platforms, gamified assessment platforms, and flexible web-based assessment platforms. These findings suggest that teachers employed different digital assessment platforms to fulfill complementary roles within classroom assessment rather than relying on a single application. The study contributes a thematic categorization of digital assessment platforms that broadens the understanding of teachers' digital assessment practices in EFL classrooms. Future research should examine these platform categories across diverse educational contexts and investigate how institutional policies and pedagogical considerations influence teachers' selection of digital assessment platforms.